Electrifying roller for electrophotographic apparatus
By using an elastomer layer containing chlorohydrin rubber, ionic conductive agent and cyclic amidine compound salt in the charged roller of the electrophotography device, the problems of rising resistance and ionic conductive agent leakage during power-on endurance are solved, and the image quality is stabilized.
Patent Information
- Application Number
- CN202380059192.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-21
AI Technical Summary
In the charged rollers of the electrophotography device, the continuous application of the electrical load caused by the power on will lead to a rise in resistance and the ionic conductive agent exudation, which in turn will lead to image defects.
The shaft body and an elastomeric layer formed on the outer peripheral surface of the shaft body are used. The elastomeric layer contains chlorohydrin rubber, an ionic conductive agent, and a salt of a cyclic amidine compound having a chlorine content of 14% or more and 19% or less, and is particularly preferred as a naphthoate salt of a cyclic amidine compound.
It effectively suppresses the increase in resistance during power-on endurance and the leakage of ionic conductive agent, ensuring the stability of image quality.
Smart Images

Figure CN119678108A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a charging roller for an electrophotographic device which is preferably used in an electrophotographic device such as a copying machine, a printer, a facsimile machine, etc. which adopts an electrophotographic method. Background Art
[0002] In a charging roller of an electrophotographic device, an ion conductive mechanism is sometimes required for the purpose of electrical uniformity, etc. For example, Patent Document 1 discloses that an ion conductive agent is blended into a base layer of a charging roller.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-132020 Summary of the invention
[0006] Problems to be solved by the invention
[0007] If the electric load caused by the continuous application of power to the charging roller, the resistance of the charging roller increases, and image defects may occur due to the reduction of charging ability. This is because if the electric load is applied to the charging roller, the ion conductive agent in the base rubber of the charging roller is polarized, and the polarization of the ion conductive agent is too fast, and the polarized anions and cations are excessively offset to the + electrode side and the - electrode side, respectively. In the center of the base rubber, the ion conductive agent becomes less and forms a part with high resistance. If the ion conductive agent is excessively increased for the purpose of suppressing excessive polarization in the base rubber, there is a risk of causing the ion conductive agent to seep out and cause image defects.
[0008] The problem to be solved by the present invention is to provide a charging roller for an electrophotographic apparatus which suppresses an increase in resistance during power-on durability and the bleeding of an ion conductive agent.
[0009] Means used to solve problems
[0010] The charging roller for an electrophotographic device according to the present invention comprises: a shaft body; and an elastic layer formed on the outer peripheral surface of the shaft body, wherein the elastic layer contains the following (a) to (c).
[0011] (a) Epichlorohydrin rubber having a chlorine content of 14% or more and 19% or less.
[0012] (b) Ion conductive agent.
[0013] (c) Salts of cyclic amidine compounds.
[0014] The (c) is preferably a naphthoate salt of a cyclic amidine compound. Based on 100 parts by mass of the (a), the content of the (c) is preferably 0.1 parts by mass or more and 5.0 parts by mass or less. Based on 100 parts by mass of the (a), the content of the (b) is preferably 0.5 parts by mass or more and 3.0 parts by mass or less. The (b) is preferably an ammonium, phosphonium or imidazolium ion conductor. The (b) is preferably an ion conductor comprising a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
[0015] (1) The charging roller for an electrophotographic device according to the present invention comprises: a shaft body; and an elastic layer formed on an outer peripheral surface of the shaft body, wherein the elastic layer contains the following (a) to (c).
[0016] (a) Epichlorohydrin rubber having a chlorine content of 14% or more and 19% or less.
[0017] (b) Ion conductive agent.
[0018] (c) Salts of cyclic amidine compounds.
[0019] (2) In the above (1), the (c) is preferably a naphthoate salt of a cyclic amidine compound.
[0020] (3) In the above (1) or (2), the content of (c) is preferably 0.1 parts by mass or more and 5.0 parts by mass or less based on 100 parts by mass of (a).
[0021] (4) In any one of the above (1) to (3), the content of (b) is preferably 0.5 parts by mass or more and 3.0 parts by mass or less based on 100 parts by mass of (a).
[0022] (5) In any one of the above (1) to (4), the above (b) is preferably an ammonium-based, phosphonium-based or imidazolium-based ion conductive agent.
[0023] (6) In any one of the above (1) to (5), the above (b) is preferably an ion conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
[0024] Effects of the Invention
[0025] According to the charging roller for an electrophotographic device involved in the present invention, since it includes a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body, and the elastic layer contains the above-mentioned (a) to (c), the increase in resistance during electrical durability and the leakage of the ion conductive agent are suppressed.
[0026] When the (c) is a naphthoate of a cyclic amidine compound, the effect of suppressing the increase in resistance during electrical durability is particularly excellent.
[0027] When the content of (c) is 0.1 to 5.0 parts by mass based on 100 parts by mass of (a), the excessive polarization of the ion conductive agent can be suppressed even when an electric load is applied by energization. In addition, the bleed-out of (c) can be suppressed.
[0028] When the content of (b) is 0.5 parts by mass or more and 3.0 parts by mass or less based on 100 parts by mass of (a), the resistance can be low and the bleeding of (b) can be suppressed.
[0029] Moreover, if the (b) is an ammonium, phosphonium or imidazolium ion conductor, since the polar group of the rubber component of (a) is easy to coordinate with the cation of the ion conductor, it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability, so the effect of suppressing the resistance increase during the electrical durability is particularly excellent. In addition, since the salt of the cyclic amidine compound of (c) is easy to coordinate with the cation of the ion conductor, it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability, so the effect of suppressing the resistance increase during the electrical durability is particularly excellent. In addition, it is easy to become a low resistance.
[0030] Moreover, the ionic conductive agent containing the sulfonate anion with fluorine atoms or the bis(sulfonyl)imide anion with fluorine atoms contains many fluorine groups in the structure, so the alkalinity of the anion itself is small, and a relatively weak ionic bond is formed with the cation. Therefore, these ionic conductive agents are easily dissociated into ions in the rubber (a), and are easy to become low resistance. In addition, these anions are all hydrophobic, and their hygroscopicity is low even in a high humidity environment. Therefore, the effect of suppressing the change of resistance caused by environmental changes is excellent. Moreover, the ionic conductive agent containing the perchlorate anion is easy to become low resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 (a) is a schematic diagram of the appearance of a charging roller for an electrophotographic device according to one embodiment of the present invention, Figure 1 (b) in the figure is its AA line cross-sectional view. DETAILED DESCRIPTION
[0032] The charging roller for an electrophotographic apparatus (hereinafter, sometimes simply referred to as a charging roller) according to the present invention will be described in detail. Figure 1 (a) is a schematic diagram of the appearance of a charging roller for an electrophotographic device according to one embodiment of the present invention, Figure 1 (b) in the figure is its AA line cross-sectional view.
[0033] The charged roller 10 includes: a shaft 12; an elastomer layer 14 formed on the outer peripheral surface of the shaft 12; and a surface layer 16 formed on the outer peripheral surface of the elastomer layer 14. The elastomer layer 14 is a layer (base layer) that becomes the base of the charged roller 10. The surface layer 16 is a layer that appears on the surface of the charged roller 10. In addition, in the charged roller of the present invention, it is also possible to have a structure without a surface layer. That is, it is also possible that the charged roller includes: a shaft 12; and an elastomer layer 14 formed on the outer peripheral surface of the shaft 12, and the outer peripheral surface of the elastomer layer 14 does not have a surface layer 16.
[0034] The shaft body 12 is not particularly limited as long as it has conductivity. Specifically, examples include a core rod made of a solid body or a hollow body made of metal such as iron, stainless steel, and aluminum. An adhesive, a primer, and the like may be applied to the surface of the shaft body 12 as needed. In other words, the elastomer layer 14 may also be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, primer, and the like may be made conductive as needed.
[0035] The elastic layer 14 contains the following (a) to (c).
[0036] (a) Epichlorohydrin rubber having a chlorine content of 14% or more and 19% or less.
[0037] (b) Ion conductive agent.
[0038] (c) Salts of cyclic amidine compounds.
[0039] As epichlorohydrin rubber, epichlorohydrin homopolymer (CO), epichlorohydrin-ethylene oxide binary copolymer (ECO), epichlorohydrin-allyl glycidyl ether binary copolymer (GCO), epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymer (GECO), etc. can be cited. Among them, from the viewpoint of having a polarity suitable for the coordination of the ion conductive agent, the excellent reactivity of the chlorine unit of the epichlorohydrin rubber with the anion part of the salt of the cyclic amidine compound, etc., the ternary system ECO is preferred. In addition, among them, ECO and GECO containing ethylene oxide as a copolymer component are more preferred in terms of easy acquisition of low resistance bodies compared to epichlorohydrin rubbers that do not contain ethylene oxide as a copolymer component. In addition, GCO and GECO containing allyl glycidyl ether as a copolymer component have double bonds, so compared with epichlorohydrin rubbers that do not contain allyl glycidyl ether as a copolymer component, it is more preferred in terms of difficulty in aging.
[0040] The chlorine content of the epichlorohydrin rubber is set to be greater than 14% and less than 19%. If the chlorine content of the epichlorohydrin rubber is less than 14%, it is difficult for the anion part of the salt of the cyclic amidine compound to react with the chlorine unit of the epichlorohydrin rubber, and the amount of the reaction part that effectively suppresses the polarization of the ions of the ion conductive agent becomes insufficient. Therefore, the resistance increase caused by the excessive polarization of the ion conductive agent cannot be suppressed. In addition, from this point of view, the chlorine content of the epichlorohydrin rubber is preferably greater than 15%, and more preferably greater than 16%. On the other hand, if the chlorine content of the epichlorohydrin rubber is greater than 19%, the chloride ions of the anions separated from the epichlorohydrin rubber react excessively with the cations of the ion conductive agent, promoting the deactivation of the ion conductive agent. As a result, the resistance increase cannot be suppressed. In addition, from this point of view, the chlorine content of the epichlorohydrin rubber is preferably less than 18%, and more preferably less than 17%.
[0041] The epichlorohydrin rubber can be crosslinked by a crosslinking agent. There is no particular limitation on the crosslinking agent. Examples of the crosslinking agent include sulfur crosslinking agents, peroxide crosslinking agents, and dechlorination crosslinking agents. These crosslinking agents can be used alone or in combination of two or more.
[0042] Examples of the sulfur crosslinking agent include sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and high-molecular polysulfide.
[0043] Examples of the peroxide crosslinking agent include peroxyketals, dialkyl peroxides, peroxyesters, ketone peroxides, peroxydicarbonates, diacyl peroxides, and hydroperoxides.
[0044] As a peroxide crosslinking agent, from the viewpoint of having a relatively high decomposition temperature and being able to be easily formed at a higher temperature, it is preferred that the decomposition temperature in the thermal storage test (BAM formula: SADT) is 60°C or higher and the 1-minute half-life temperature is 150°C or higher. More preferably, the 1-minute half-life temperature is 160°C or higher, and further preferably, the 1-minute half-life temperature is 170°C or higher. On the other hand, from the viewpoint of excellent crosslinking speed, the 1-minute half-life temperature is preferably 200°C or lower. More preferably, the 1-minute half-life temperature is 190°C or lower, and further preferably, the 1-minute half-life temperature is 180°C or lower.
[0045] Preferred peroxide crosslinking agents include peroxyketals, dialkyl peroxides, and peroxyesters. Examples of peroxyketals include 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, and n-butyl 4,4-di(tert-butylperoxy)valerate. Examples of dialkyl peroxides include di(2-tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne. Examples of the peroxyester include tert-butyl peroxybenzoate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxylaurate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and tert-hexyl peroxyisopropyl monocarbonate. Among them, di(2-tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 1,1-di(tert-butylperoxy)cyclohexane are preferred from the viewpoints that unreacted components are unlikely to remain and the boiling point of the decomposition product is relatively low, making it easy to remove the decomposition product.
[0046] Examples of the dechlorination crosslinking agent include dithiocarbonate compounds, and more specifically, include quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, and 5,8-dimethylquinoxaline-2,3-dithiocarbonate.
[0047] The amount of the crosslinking agent is preferably within a range of 0.1 to 2 parts by mass, more preferably 0.3 to 1.8 parts by mass, and even more preferably 0.5 to 1.5 parts by mass based on 100 parts by mass of the epichlorohydrin rubber from the viewpoint of preventing bleeding.
[0048] From the viewpoint of making the elastic body layer 14 easy to have low hardness, the content of the peroxide crosslinking agent is preferably 6 parts by mass or less based on 100 parts by mass of the epichlorohydrin rubber in the conversion of the peroxide original body. It is more preferably 5 parts by mass or less, and further preferably 4 parts by mass or less. In addition, from the viewpoint of excellent crosslinking degree of the rubber and not easy to age, it is preferably 0.2 parts by mass or more based on 100 parts by mass of the epichlorohydrin rubber in the conversion of the peroxide original body. It is more preferably 0.4 parts by mass or more, and further preferably 0.6 parts by mass or more.
[0049] There is no particular limitation on the ion conductive agent. Any ion conductive agent used in the field of electronic photographic equipment is sufficient. Examples of the ion conductive agent include quaternary ammonium salts, quaternary phosphonium salts, imidazolium salts, borates, surfactants, etc. Among them, quaternary ammonium salts, quaternary phosphonium salts, and imidazolium salts are particularly preferred.
[0050] Examples of the cation of the quaternary ammonium salt include quaternary ammonium salts having one or more alkyl or aryl groups having carbon atoms of about 1 to 18 (methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.). The alkyl or aryl group of the cation of the quaternary ammonium salt preferably has carbon atoms of 1 to 10. Examples of the anion of the quaternary ammonium salt include F - , Cl - Br - ,I - Halogen ions, ClO4 - 、BF4 - PF6 - 、SO4 2- 、HSO4 - 、C2H5SO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - CF3(CF2)3SO3 - 、(CF3SO2)3C - CF3(CF2)2COO - As the anion of the quaternary ammonium salt, ClO4 is more preferred - 、(CF3SO2)2N - CF3SO3 - wait.
[0051] Examples of quaternary phosphonium salt cations include quaternary phosphonium salts having one or more alkyl or aryl groups with carbon atoms of about 1 to 18 (methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.). The alkyl or aryl group of the quaternary phosphonium salt cation preferably has carbon atoms of 1 to 10. Examples of quaternary phosphonium salt anions include F - , Cl - Br - ,I - Halogen ions, ClO4 - 、BF4 - PF6 - 、SO4 2- 、HSO4 - 、C2H5SO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - CF3(CF2)3SO3 -、(CF3SO2)3C - CF3(CF2)2COO - As the anion of the quaternary phosphonium salt, ClO4 is more preferred - 、(CF3SO2)2N - CF3SO3 - wait.
[0052] Examples of the imidazolium salt include unsubstituted imidazolium salts, 1-alkylimidazolium salts, 3-alkylimidazolium salts, 1,3-dialkylimidazolium salts, and 1,2,3-trialkylimidazolium salts. More specifically, for example, 1-methylimidazolium salt, 1,3-dimethylimidazolium salt, 1,3-diethylimidazolium salt, 1,3-dipropylimidazolium salt, 1,3-dibutylimidazolium salt, 1,3-dicyclohexylimidazolium salt, 1-ethyl-3-methylimidazolium salt, 1-propyl-3-methylimidazolium salt, 1-butyl-3-methylimidazolium salt, 1-hexyl-3-methylimidazolium salt, 1-ethyl-2,3-dimethylimidazolium salt, 1-propyl-2,3-dimethylimidazolium salt, 1-butyl-2,3-dimethylimidazolium salt, etc. can be mentioned. As the anion of the imidazolium salt, F can be mentioned. - , Cl - Br - ,I - Halogen ions, ClO4 - 、BF4 - PF6 - 、SO4 2- 、HSO4 - 、C2H5SO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - CF3(CF2)3SO3 - 、(CF3SO2)3C - CF3(CF2)2COO - As the anion of the imidazolium salt, ClO4 is more preferred - 、(CF3SO2)2N - CF3SO3 - wait.
[0053] As borates, for example, borates having one or more alkyl or aryl groups having a carbon number of about 1 to 18 (methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.) and containing alkali metal ions or alkaline earth metal ions such as lithium ions, sodium ions, potassium ions, and calcium ions can be shown.
[0054] From the viewpoints of being easy to become low resistance and easy to suppress the resistance rise during power-on durability, the content of the ion conductive agent is preferably 0.5 parts by mass or more based on 100 parts by mass of the chlorohydrin rubber. More preferably, it is 0.7 parts by mass or more, and further preferably, it is 1.0 parts by mass or more. In addition, from the viewpoints of being easy to suppress the seepage of the ion conductive agent, it is preferably 3.0 parts by mass or less based on 100 parts by mass of the chlorohydrin rubber. More preferably, it is 2.5 parts by mass or less, and further preferably, it is 2.0 parts by mass or less.
[0055] The cyclic amidine compound is a cyclic compound containing an amidine structure in its structure. In the salt of the cyclic amidine compound, the anion side reacts with the chlorine unit of the epichlorohydrin rubber. Since the reaction part has a moderate polarity that is easy to coordinate with the ions (cations) of the ion conductive agent, it is possible to suppress the excessive polarization of the ion conductive agent and suppress the resistance rise during the power-on durability. From the viewpoint of excellent reactivity with the chlorine unit of the epichlorohydrin rubber, the anion side of the salt of the cyclic amidine compound preferably has a hydroxyl group and a carboxyl group. In the salt of the cyclic amidine compound, a part (alkaline part) of the cyclic amidine compound functions as a catalyst that improves the reactivity of the anion side of the salt of the cyclic amidine compound with the chlorine unit. Therefore, relative to the epichlorohydrin rubber, it is effective when it is coordinated with naphthoic acid, etc., instead of a monomer, but as a naphthoate salt of the cyclic amidine compound, etc.
[0056] As the cyclic amidine compound, from the viewpoint of availability, a bicyclic amidine compound is preferred. As the cyclic amidine compound, diazabicycloundecene (1,8-diazabicyclo (5.4.0) undec-7-ene), diazabicyclononene (1,5-diazabicyclo (4.3.0)-5-nonene) and the like can be cited. As the cyclic amidine compound, from the viewpoint of catalyst function, storage stability and the like, diazabicycloundecene is more preferred.
[0057] As the salt of the cyclic amidine compound, naphthoic acid salts of the cyclic amidine compound, phenolic resin salts of the cyclic amidine compound, aliphatic carboxylates, phenol salts, borates, etc. are preferred from the viewpoint of excellent reactivity with the chlorine unit of the epichlorohydrin rubber. Among them, naphthoic acid salts of the cyclic amidine compound are particularly preferred from the viewpoint of particularly excellent effect of suppressing the increase in resistance during electrical durability.
[0058] From the viewpoint that the effect of suppressing excessive polarization of the ion conductive agent is excellent even if the electric load caused by energization is applied, the content of the salt of the cyclic amidine compound is preferably 0.1 parts by mass or more based on 100 parts by mass of the chlorohydrin rubber. More preferably, it is 0.3 parts by mass or more, and more preferably, it is 0.5 parts by mass or more. In addition, from the viewpoint that the oozing out of the salt of the cyclic amidine compound is suppressed, it is preferably 5.0 parts by mass or less based on 100 parts by mass of the chlorohydrin rubber. More preferably, it is 4.0 parts by mass or less, and more preferably, it is 3.0 parts by mass or less.
[0059] The rubber composition may contain other additives as required. Examples of other additives include electronic conductive agents, lubricants, antioxidants, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, fillers, dispersants, pigments, and mold release agents.
[0060] Examples of the electron conductive agent include carbon black, graphite, conductive titanium oxide, conductive zinc oxide, and conductive tin oxide.
[0061] The thickness of the elastic layer 14 is not particularly limited, but is preferably within a range of 0.1 to 10 mm, more preferably within a range of 0.5 to 5 mm, and even more preferably within a range of 1 to 3 mm.
[0062] The volume resistivity of the elastic layer 14 is not particularly limited, but is preferably 10 2 ~10 10 Ω·cm, more preferably 10 3 ~10 9 Ω·cm, more preferably 10 4 ~10 8 In the range of Ω·cm.
[0063] The surface layer 16 can function as a protective layer of the roller surface. The surface layer 16 preferably contains a polymer component such as polyamide, polyurethane, acrylic resin, alkyd resin, phenolic resin, fluorine resin, silicone resin, or a modified body thereof as a main material. As a modified group in the modified body, for example, N-methoxymethyl, silicone group, fluorine group, etc. can be listed. These polymer components can be included as a surface material alone, or two or more can be included in combination. The polymer component of the surface layer 16 can also be cross-linked.
[0064] In the surface layer 16, in order to impart conductivity, conductive agents such as carbon black, graphite, conductive titanium oxide, conductive zinc oxide, conductive tin oxide, ion conductive agents (quaternary ammonium salts, borates, surfactants, etc.) can be appropriately added. In addition, various additives can also be appropriately added as needed. In addition, in order to ensure surface roughness, roughness forming particles can also be added.
[0065] The roughness forming particles form surface irregularities in the surface layer 16. Examples of the roughness forming particles include resin particles, silica particles, and the like. Examples of the resin particles include urethane particles, silicone particles, and acrylic particles. The average particle size of the roughness forming particles is preferably within a range of 3 to 50 μm. The average particle size of the roughness forming particles can be calculated by the median particle size using a laser diffraction particle size distribution measuring device.
[0066] The thickness of the surface layer 16 is not particularly limited, but is preferably in the range of 0.01 to 100 μm, more preferably in the range of 0.1 to 20 μm, and further preferably in the range of 0.3 to 10 μm. The volume resistivity of the surface layer 16 is preferably 10 7 ~10 12 Ω·cm, more preferably 10 8 ~10 11 Ω·cm, more preferably 10 9 ~10 10 In the range of Ω·cm.
[0067] The charging roller 10 can be manufactured, for example, as follows. First, the shaft 12 is coaxially arranged in the hollow part of the roller forming mold, and a rubber composition is injected. After heating and curing, the rubber composition is demolded or extruded on the surface of the shaft 12, thereby forming an elastic body layer 14 on the outer periphery of the shaft 12. Next, a surface layer forming composition is applied to the outer periphery of the formed elastic body layer 14, and ultraviolet irradiation and heat treatment are performed as needed to form a surface layer 16. In this way, the charging roller 10 can be manufactured.
[0068] The surface layer forming composition is composed of the material containing the above-mentioned main material, conductive agent, and other additives contained as needed. As other additives, crosslinking agents, leveling agents, surface modifiers, etc. of polymer components can be listed. From the viewpoints of adjusting viscosity, the surface layer forming composition can appropriately include organic solvents such as methyl ethyl ketone, toluene, acetone, ethyl acetate, butyl acetate, methyl isobutyl ketone (MIBK), THF, DMF, methanol, ethanol and other water-soluble solvents. As a coating method, various coating methods such as roller coating, dipping, spraying can be applied.
[0069] According to the charged roller 10 of the above structure, the elastomer layer 14 contains (a) chlorohydrin rubber having a chlorine content of 14% or more and 19% or less, (b) an ion conductor, and (c) a salt of a cyclic amidine compound, so that the resistance increase during the energized durability test and the seepage of the ion conductor are suppressed. It is speculated that this is due to the following mechanism. That is, the anion side of the salt of the cyclic amidine compound reacts with the chlorine unit of the chlorohydrin rubber, and the ions (cations) of the ion conductor coordinate with the reaction part, so that even if the electric load caused by the energization is applied, the excessive polarization of the ion conductor is suppressed. As a result, the resistance increase during the energized durability test is suppressed. In addition, since the excessive polarization of the ion conductor is not suppressed by the increase of the ion conductor, the seepage of the ion conductor is also suppressed.
[0070] If the chlorine content of the epichlorohydrin rubber is less than 14%, the anion part in the salt of the cyclic amidine compound is difficult to react with the chlorine unit of the epichlorohydrin rubber, and the amount of the reaction part that effectively suppresses the polarization of the ions of the ion conductive agent becomes insufficient. Therefore, the resistance increase caused by the excessive polarization of the ion conductive agent cannot be suppressed. On the other hand, if the chlorine content of the epichlorohydrin rubber is greater than 19%, the chloride ions of the anions separated from the epichlorohydrin rubber react excessively with the cations of the ion conductive agent, promoting the deactivation of the ion conductive agent. As a result, the resistance increase cannot be suppressed. Therefore, the chlorine content of the epichlorohydrin rubber is set to be greater than 14% and less than 19%.
[0071] Moreover, if the ion conductor is an ammonium series, a phosphonium series or an imidazolium series, since the polar groups of the chlorohydrin rubber are easily coordinated with the cations of the ion conductor, it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability, so the effect of suppressing the resistance increase during the electrical durability is particularly excellent. In addition, since the salt of the cyclic amidine compound is easy to coordinate with the cations of the ion conductor, it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability, so the effect of suppressing the resistance increase during the electrical durability is particularly excellent. In addition, it is easy to become a low resistance.
[0072] And, if the ionic conductive agent is an ionic conductive agent comprising a sulfonate anion with a fluorine atom or a bis(sulfonyl)imide anion with a fluorine atom, then because a lot of fluorine groups are included in the structure, the alkalinity of the anion itself is small, and a relatively weak ionic bond is formed with the cation. Therefore, these ionic conductive agents are easily dissociated into ions in the rubber of chlorohydrin rubber, and are easily low in resistance. In addition, these anions are all hydrophobic, and hygroscopicity is also low even in a high humidity environment. Therefore, the effect of suppressing the change of resistance caused by environmental changes is excellent. And, the ionic conductive agent comprising perchlorate anion is easy to become low resistance.
[0073] Example
[0074] Hereinafter, the present invention will be described in detail using Examples and Comparative Examples.
[0075] (Example 1)
[0076] <Preparation of rubber composition>
[0077] 100 parts by mass of epichlorohydrin rubber <1>, 3 parts by mass (1.2 parts by mass in terms of original amount) of a peroxide crosslinking agent (Peroxymon F40), 5 parts by mass of an acid binder, 1.0 parts by mass of an ion conductive agent, and 2 parts by mass of a salt of a cyclic amidine compound (naphthoate of diazabicycloundecene) were stirred and mixed in a stirrer to prepare a rubber composition.
[0078] <Formation of elastic layer>
[0079] A mandrel (6 mm in diameter) was placed in the mold, the rubber composition was injected at 120°C, and heated at 175°C for 30 minutes to crosslink the rubber composition. After that, the mold was cooled and released, and an elastic layer with a thickness of 2 mm was formed on the outer periphery of the mandrel.
[0080] <Formation of the surface layer>
[0081] 100 parts by mass of N-methoxymethylated nylon ("EF30T" manufactured by Nagase Chemtex), 60 parts by mass of conductive tin oxide ("S-2000" manufactured by Mitsubishi Materials), 1 part by mass of citric acid, and 300 parts by mass of methanol were mixed to prepare a surface layer forming composition. Next, the surface layer forming composition was roll-coated on the surface of the elastomer layer and heated at 120°C for 50 minutes to form a surface layer with a thickness of 10 μm on the outer periphery of the elastomer layer. Thus, a charging roller was prepared.
[0082] (Example 2)
[0083] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that the type of the epichlorohydrin rubber was changed.
[0084] (Examples 3-4)
[0085] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that the type of the salt of the cyclic amidine compound was changed.
[0086] (Examples 5 to 7)
[0087] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that the blending amount of the salt of the cyclic amidine compound was changed.
[0088] (Examples 8 to 9)
[0089] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that the blending amount of the ion conductive agent was changed.
[0090] (Comparative Example 1)
[0091] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that the salt of the cyclic amidine compound was not blended.
[0092] (Comparative Example 2)
[0093] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 2 except that the salt of the cyclic amidine compound was not added and the amount of the ion conductive agent added was changed.
[0094] (Comparative Example 3)
[0095] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that the type of the epichlorohydrin rubber was changed.
[0096] (Comparative Example 4)
[0097] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that a cyclic amidine compound was blended instead of a salt of the cyclic amidine compound.
[0098] (Comparative Example 5)
[0099] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Example 1 except that naphthoic acid was added instead of the salt of the cyclic amidine compound.
[0100] The following materials were prepared as materials for the rubber composition.
[0101] ·Epoxyhydrin rubber <1> (chlorine content 14%): "Epyon 301" manufactured by Osaka Soda
[0102] ·Epoxy Hydrin Rubber <2> (chlorine content 19%): "Hydrin T3108" manufactured by ZEON Japan
[0103] ·Epoxy Hydrin Rubber <3> (chlorine content 28%): "Hydrin T3105" manufactured by ZEON, Japan
[0104] · Cross-linking agent: NOF Corporation's "Peroxymon F40"
[0105] ·Diazabicycloundecene salt<1>: 1,8-diazabicyclo(5.4.0)undec-7-ene, 3-hydroxy-2-naphthoate
[0106] ·Diazabicycloundecene salt<2>: 1,8-diazabicyclo(5.4.0)undec-7-ene phenolic resin salt
[0107] ·Diazabicyclononene salt: 1,5-diazabicyclo(4.3.0)-5-nonene phenolic resin salt
[0108] ·Diazabicycloundecene: 1,8-diazabicyclo(5.4.0)undec-7-ene
[0109] ·Naphthoic acid: 3-hydroxy-2-naphthoic acid
[0110] Acid binding agent: "DHT-4A" manufactured by Kyowa Chemical Industry
[0111] Ion conductive agent: Tetrabutylammonium trifluoromethanesulfonate manufactured by Tokyo Chemical Industry.
[0112] The produced charging rollers were evaluated for resistance change during power-on durability and bleed-out of the ion conductive agent.
[0113] <Evaluation method of on-resistance change>
[0114] exist A load of 700g was applied to each end of the charged roller on the metal drum, and the metal drum was rotated at 90rpm. The power-on test was carried out with a cumulative current of 120C (power-on conditions: 1000Hz, 0.19kVpp, 1500μA constant current control). The resistance values before and after the test were obtained, and the resistance change was calculated in bits. The case where the resistance change is less than 0.3 bits is "A", the case where the resistance change is more than 0.3 bits and less than 0.5 bits is "B", the case where the resistance change is more than 0.5 bits and less than 1.0 bits is "C", and the case where the resistance change is more than 1.0 bits is "D".
[0115] <Bleeding evaluation method>
[0116] After the charging roller was left in a hot and humid environment at 40° C. for 30 days, the presence or absence of oozing on the surface of the charging roller was observed. A case where no oozing was observed was rated as “◯”, and a case where oozing was observed was rated as “×”.
[0117]
[0118] The embodiment forms an elastic layer by a rubber composition containing chlorohydrin rubber having a chlorine content of 14% or more and 19% or less, an ion conductive agent, and a salt of a cyclic amidine compound. According to the embodiment, during the electrical durability test, the increase in resistance caused by the polarization of the ion conductive agent is small. In addition, no leakage of the ion conductive agent is observed.
[0119] On the other hand, in Comparative Example 1, the rubber composition of the elastomer layer containing epichlorohydrin rubber and an ion conductive agent does not contain a salt of a cyclic amidine compound. According to Comparative Example 1, the resistance increase during the electrical durability test is large. In Comparative Example 2, the rubber composition of the elastomer layer containing epichlorohydrin rubber and an ion conductive agent does not contain a salt of a cyclic amidine compound. In addition, the amount of the ion conductive agent is more than that of Comparative Example 1. According to Comparative Example 2, the resistance increase during the electrical durability test is suppressed to be smaller than that of Comparative Example 1, but the leakage of the ion conductive agent is not suppressed. In Comparative Example 3, the chlorine content of the epichlorohydrin rubber in the rubber composition of the elastomer layer is high. According to Comparative Example 3, the resistance increase during the electrical durability test is large. In Comparative Example 4, the rubber composition of the elastomer layer containing epichlorohydrin rubber and an ion conductive agent does not contain a salt of a cyclic amidine compound, but contains a cyclic amidine compound. According to Comparative Example 4, the resistance increase during the electrical durability test is large. In Comparative Example 5, the rubber composition of the elastic layer containing the epichlorohydrin rubber and the ion conductive agent contained naphthoic acid instead of the salt of the cyclic amidine compound. According to Comparative Example 5, the resistance increase during the electrical durability test was large.
[0120] Therefore, according to the embodiments and comparative examples, by forming the elastic layer of the charged roller from a rubber composition containing chlorohydrin rubber having a chlorine content of greater than 14% and less than 19%, an ion conductive agent, and a salt of a cyclic amidine compound, the increase in resistance during electrical durability and the leakage of the ion conductive agent are suppressed.
[0121] Moreover, in the comparison between the embodiments, it can be seen from Examples 1, 3, and 4 that among the salts of the cyclic amidine compound, the naphthoate of the cyclic amidine compound has a better effect of suppressing the resistance increase during the power-on durability. In addition, it can be seen from Examples 1, 5, 6, and 7 that if the amount of the salt of the cyclic amidine compound is 0.5 parts by mass or more and 5 parts by mass or less based on 100 parts by mass of the chlorohydrin rubber, the effect of suppressing the resistance increase during the power-on durability is better. In addition, it can be seen from Examples 1, 8, and 9 that if the amount of the ion conductive agent is 1.0 parts by mass or more and 3.0 parts by mass or less based on 100 parts by mass of the chlorohydrin rubber, the effect of suppressing the resistance increase during the power-on durability is better.
[0122] As mentioned above, although embodiment and Example of this invention were described, this invention is not limited at all to the said embodiment and Example, Various changes can be made within the range which does not deviate from the summary of this invention.
[0123] Description of Reference Numerals
[0124] 10: Charging roller;
[0125] 12: Axis;
[0126] 14: Elastomer layer;
[0127] 16: Surface.
Claims
1. A charging roller for an electrophotographic device, wherein: The charging roller for an electrophotographic device comprises: Axle; and an elastic layer formed on the outer peripheral surface of the shaft body, The elastomer layer contains the following (a) to (c): (a) epichlorohydrin rubber having a chlorine content of not less than 14% and not more than 19%, (b) an ion conductive agent, (c) Salts of cyclic amidine compounds.
2. The charging roller for an electrophotographic apparatus according to claim 1, wherein The (c) is a naphthoate salt of a cyclic amidine compound.
3. The charging roller for an electrophotographic apparatus according to claim 1 or 2, wherein: The content of the (c) is 0.1 parts by mass or more and 5.0 parts by mass or less based on 100 parts by mass of the (a).
4. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 3, wherein The content of (b) is 0.5 parts by mass or more and 3.0 parts by mass or less based on 100 parts by mass of (a).
5. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 4, wherein The (b) is an ammonium-based, phosphonium-based or imidazolium-based ion conductive agent.
6. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 5, wherein The (b) is an ion conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
Citation Information
Patent Citations
Rubber composition for conductive roller
JP2002132020A